(untitled) (LACCEI, 2024)
Density functional theory (DFT) calculations can guide the design of efficient and selective catalysts for converting biomass-derived feedstocks to fuels and chemicals. In this work, we performed systematic DFT calculations with specific treatment of van der Waals forces to analyze the structure and functionality of zeolites substituted with metals. The catalytic activity of Sn-BEA and the interaction of this catalyst with different solvents were studied. Through these calculations, we intended to analyze the effect of solvent on the reaction mechanism to turn fructose into dihydroxyacetone (DHA) and glyceraldehyde (GLA). The interactions of reactants, products, and solvent molecules with Sn-BEA will provide insight into the catalytic properties of these systems, and transition state calculations will guide on the selection of the best solvent for this reaction